„Dżafar z Bagdadu” Janusza Makarczyka jako cenne źródło wiedzy o historii i literaturze arabskiej epoki Abbasydów - Olkusz, Wiesław (Ruch Literacki, 2018)
This article deals with Janusz Makarczyk’s bestselling historical romance Jafar of Baghdad, first published in 1950. Makarczyk had a varied career as a journalist, travel writer of the ‘globtrotter school’, military officer, diplomat and academic; his deep involvement with the Middle East and Arab history began in the 1926 when he was sent to the Polish consulate in Jerusalem. The life of Jafar ibn Yahya provided him not only with enough material for a gripping story of love and romance but also a pretext for painting a broad canvas of historical events and personages. Addressed to younger readers, the book is didactic in the sense that it offers them basic information about Islam (e.g. the division between the sunni and the shia) as well as lots of facts about the Arab world at the peak of the Abbasid Age (e.g. Harun al-Rashid and the struggle for his succession; rise and fall of the powerful Barmakid family, Harun al-Rashid’s half-sister Abassa; the great Islamic jurists Malik ibn Anas, Muhammad al-Shaybani and Al-Shafi ‘i; an assortment of poets and scholars, including the translator Ibn al-Muqaffa). In addition to countless allusions to the Book of the Thousand Nights and One Night, the narrative is encrusted with explicit and covert quotes from the Qur’an, Arabic adages and proverbs (32), the poems of Abu-l-’Atahiya and Abu Nuwas. The writer is aware that the allusions and learned references need to be contextualized in a way that is functional and that their incorporation into the main text must be handled with maximum flexibility. The great popularity of Jafar of Baghdad in its time can be taken as proof that Makarczyk did succeed in bringing the two functions of his novel, the cognitive and the aesthetic – to instruct and to please – into a harmonious whole.
Keywords: Polish literature of the 20th century; historical romance; the Orient and Islam in popular fiction; Abbasid Empire; Harun al-Rashid; Jafar ibn Yahya; intertextuality; Janusz Makarczyk (1901–1960)